Evidence for T Cell Help in the IgG Response against Tandemly Repetitive Trypanosoma cruzi B13 Protein in Chronic Chagas Disease Patients - Duranti, Marcia (Hindawi Publishing Corporation, 2012)
The tandemly repetitive Trypanosoma cruzi B13 protein is an immunodominant antigen among Chagas disease patients. Such repetitive domains may behave as T-independent antigens. However, T cells can recognize B13 epitopes in an HLA class II-restricted fashion and could potentially provide cognate T cell help and boost antibody titers. We assessed whether the presence of HLA class II molecules able to present B13 epitopes to T cells could affect anti-B13 IgG levels in a cognate fashion, in both major clinical forms of chronic Chagas disease. We found no difference between anti-B13 IgG antibody levels between patients carrying HLA class II molecules associated to T cell responses or other alleles. The predominant anti-B13 IgG subclass was IgG1, with negligible IgG2, suggesting a T-dependent, noncognate help for antibody production. In addition, the finding of increased anti-B13 IgG levels in sera from CCC patients indicates that clinical presentation is associated with increased anti-B13 antibody levels.